Estudo da variabilidade genética intraespecífica de Leishmania (Leishmania) infantum em amostras de cães e humanos - Thais Almeida Marques da Silva (2013)
Visceral leishmaniasis (VL) is a disease distributed worldwide and potentially fatal to humans if not diagnosed and early treated. In addition to human, other mammals are also affected, especially dogs in the urban context, which are the major reservoir of the disease. Individuals showing human immunodeficiency virus (HIV) infection are also susceptible to VL and deserve more attention. The city of Belo Horizonte, Minas Gerais state, has one of the highest lethality rates for VL in humans in Brazil and a high prevalence for the disease in dogs. Leishmania (Leishmania) infantum is the etiological agent for VL in Brazil and the aim of this work was to study the intraspecific genetic variability of Leishmania from human and dogs cases in Belo Horizonte, and some other municipalities in Minas Gerais state, applying PCR-RFLP with different DNA targets: kDNA and gp63. In this work were evaluated 47 DNA samples extracted from clinical specimens (n = 35) and L. infantum culture (n = 12), and these samples were from three different groups: adults (n = 16), children (n = 18) and dogs (n = 13). The samples were amplified for kDNA using the primers MC1 and MC2, specific to the Leishmania donovani complex, which generate a fragment of 447pb (base pairs). For gp63 glycoprotein the primers used were SG1 and SG2, which generate a fragment of 1330bp. To perform the kDNA RFLP five restriction enzymes were used: VspI, RsaI, BglII, DdeI and Hpa II. The gp63 glycoprotein RFLP was performed with two enzymes: Hinc II and TaqI. The results obtained with RsaI, BglII, DdeI, Hpa II, HincII and TaqI restriction enzymes proved to be monomorphic. Two distinct profiles were identified with the VspI enzyme: Type I (revealed by 46 DNA samples) and Type II (shown for only one DNA sample evaluated in the study). This same result was also seen by phenogram analysis, constructed with binary matrix and neighbor-joining clustering. The variable sample was from an adult who presented classic VL and is resident of Minas Novas city, Minas Gerais state, municipality not belonging to the Metropolitan Region of Belo Horizonte. These findings reveal there is a high degree of homogeneity among Leishmania from human and dogs in Belo Horizonte, and some other municipalities in Minas Gerais state, Brazil.